Proposed Sarawak rainforest exploratorium and research center at Kubah National Park, Kuching, Sarawak - Pamnan @ Ramnan, Nazrin; Abdullah, Fadzidah (2020)
Forests play a significant role in maintaining the balance cycle of our ecosystems. It consists of rich biodiversity, that is not only for animals and plants but also a place for humans to explore and benefit from its resources – such as timber, water, herbs, gold and oil. The rainforests in Eastern Malaysia are believed to be the oldest in the world and host the most biologically diverse forests in the world. However, the Eastern Malaysian rainforests are now in danger of disappearing due to deforestation. Excessive human activities is causing this deforestation, and researchers consider that this is the most significant threat that is harming the forest and its ecosystem. Deforestation is also known to destroy the existing animal habitat and contribute to the rise in global warming and climate change. Due to uncontrolled deforestation, the native Indigenous peoples communities who live in the Eastern Malaysian rainforests are also loosing their sources of monetary income, as well as their cultural identity. Thence, there is a need to have a design solution to protect these Indigenous peoples’ economic resources and cultural identities. The proposed architectural solution, considered in this paper, derives from an Exploratorium integrated with a research centre. This proposed facility, with its series of forest discovery spaces, would create awareness amongst the international and Malaysian domestic public on the significance of conserving this rainforest; to encourage the public to experience this unique tropical rainforest ecosystem; and, to enhance public understanding of the cultures of these native communities. Several research steps have been undertaken to analyse the spatial requirements for this Exploratorium proposal that includes a literature review, case study observations and expert interviews. The proposed Exploratorium would have facilities that reflect the culture of the place, including interactive galleries, treehouses, travel pods, and a watching tower. In short, designing the Exploratorium reconnects the division between human and nature, and simultaneously produces sustainable community and environment